ANALISIS KONFLIK TOKOH DALAM NOVEL IAM SAHRAZA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Yuniarti, Yuniarti; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is about the conflicts experienced by the characters in the story line by presenting conflicts that arise within themselves and something that exists outside of themselves. The problem in this study is how internal and external conflict with the characters and the implementation of this research in learning Indonesian. The purpose of this study is to describe the internal and external conflicts in figures and the implementation of this research in learning Indonesian using the novel I am Sarahza by Hanum Salsabiela Rais and Rangga Almahendra. The benefits in this study are divided into two, namely theoretical benefits and practical benefits.The theory used in this research is the structure of novel builders, conflict, psychology in literary works, and literary learning in schools. This research uses descriptive method, the form of this research is qualitative and uses a behavioristic psychology approach.Â Keywords:Analysis, Character Conflict, Novel